Պետական կադրային քաղաքականությունը ՀՀ-ում քաղաքական էլիտայի հավաքագրման գործոն - Ալթունյան, Կատերինա (YSU Journal of International Affairs, 2017)
The article analyzes one of the most important problems of the public administration of the Republic of Armenia (RA). The research subject is the public personnel policy as one of the main mechanisms of formation and recruitment of political elite. Specifically, the problem involves the study of the public service system,its functionality. The study is an attempt to justify the necessity of introducing a unified public personnel policy in the public service system, which, in turn, will help to announce the principles of political elite formation and recruitment processes in the Republic of Armenia. The article highlights the role of the political elite as a group of politicians and high-ranking officials managing, controlling and leading the sociopolitical processes in Armenian society.
Keywords: political elite, effectiveness of public administration, personnel policy, civil service, channels of recruitment, high-ranking officials, state body, career